The evolving role of novel and next generation therapies in the management of multiple myeloma: relapse refractory multiple myeloma 2 - Richardson, Paul G. (Henry Stewart Talks, 2019)
T-cell therapy strategies for Multiple Myeloma, Cell-based Myeloma vaccines, Antibody-drug conjugates, Continuing evolution of Multiple Myeloma treatment